1999
DOI: 10.1161/01.str.30.8.1598
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Serum Neuron-Specific Enolase

Abstract: Background and Purpose-The prediction of neurological outcome in comatose cardiac arrest survivors has enormous ethical and socioeconomic implications. The purpose of the present study was to investigate the prognostic relevance of the time course of serum neuron-specific enolase (NSE) as a biochemical marker of hypoxic brain damage. Methods-Serial analysis of serum NSE levels was performed in 56 patients resuscitated from witnessed, nontraumatic, normothermic, in-or out-of-hospital cardiac arrest. The neurolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(42 citation statements)
references
References 55 publications
3
33
0
5
Order By: Relevance
“…Alternatively, high serum NSE levels may reflect the extent of the neuronal damage. One piece of evidence which can support this hypothesis is the relationship between the degree of neuronal damage and the serum NSE level following a cerebral stroke (Cunningham et al, 1991(Cunningham et al, , 1996DeGiorgio et al, 1995DeGiorgio et al, , 1999Fogel et al, 1997;Missler et al, 1997;Martens et al, 1998;Buttner et al, 1999;Schoerkhuber et al, 1999;Wunderlich et al, 1999) or other neuronal brain damage (DeGiorgio et al, 1995(DeGiorgio et al, , 1999Fogel et al, 1997;Martens et al, 1998; Buttner et al, 1999;Schoerkhuber et al, 1999). In these diseases, the serum NSE level exhibits a prognostic indication inasmuch as studies have found a close relationship between the volume of affected neuronal tissue and the serum NSE level (Cunningham et al, 1991(Cunningham et al, , 1996Missler et al, 1997;Wunderlich et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, high serum NSE levels may reflect the extent of the neuronal damage. One piece of evidence which can support this hypothesis is the relationship between the degree of neuronal damage and the serum NSE level following a cerebral stroke (Cunningham et al, 1991(Cunningham et al, , 1996DeGiorgio et al, 1995DeGiorgio et al, , 1999Fogel et al, 1997;Missler et al, 1997;Martens et al, 1998;Buttner et al, 1999;Schoerkhuber et al, 1999;Wunderlich et al, 1999) or other neuronal brain damage (DeGiorgio et al, 1995(DeGiorgio et al, , 1999Fogel et al, 1997;Martens et al, 1998; Buttner et al, 1999;Schoerkhuber et al, 1999). In these diseases, the serum NSE level exhibits a prognostic indication inasmuch as studies have found a close relationship between the volume of affected neuronal tissue and the serum NSE level (Cunningham et al, 1991(Cunningham et al, , 1996Missler et al, 1997;Wunderlich et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…To examine this, we measured exchange of the dimeric enzyme NSE, the neuronal form of the glycolytic enzyme enolase (2-phospho-D-glycerate hydrolase), which is located almost exclusively within neuronal cell bodies, axons, and neuroendocrine cells (Schmechel et al, 1978). Its appearance across the cerebral circulation would therefore reflect parenchymal tissue injury in direct proportion to the extent of damage (Schoerkhuber et al, 1999). Thus, the lack of exchange observed in the current study combined with previous reports that have consistently failed to document any increase in the systemic (Bailey et al, 2009b), cerebrospinal fluid (Bailey et al, 2006), and transcerebral (Bailey et al, 2009d) concentration of the astrocytic protein S100b, a peripheral biomarker of blood-brain barrier damage, confirms that cerebral free radical formation proceeds in hypoxia without compromizing neurovascular integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Many attempts have been made at identifying serum or plasma protein markers of stroke, including MMP9, GFAP, S100 proteins, neuronspecific enolase, N-acetyl-aspartic acid and many others (Ali et al, 2001(Ali et al, , 2000Bertsch et al, 2001;Buttner et al, 1999Buttner et al, , 1997Castellanos et al, 2003;Elting et al, 2000;Herrmann et al, 2000;Lindsberg and Grau, 2003;Lynch et al, 2004;Martens et al, 1998;Montaner et al, 2003a, b;Persson et al, 1987;Ribo et al, 2004;Rosen et al, 1998;Schoerkhuber et al, 1999;Smith et al, 2004;Stevens et al, 1999;Strachan et al, 1999;Sulter et al, 1998;Ueda et al, 1995;Vila et al, 2000). Indeed, MMP9, alone or with a panel of four proteins, can predict stroke with high accuracy Montaner et al, 2003b).…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%